Penelitian Kasus Trachoma pada Murid Sekolah Dasar - Mu'tasimbillah Ghozi Mu'tasimbillah Ghozi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1980)
Trachoma is a specific communicable keratoconjunctivitis, usually of chronic evolution caused by an agent belonging to the psittacosis - lymphogranuloma - trachoma group of atypical viruses and characterized by follicles, papillary hyperplasia, pannus, and in its later stages, by cicatrizadon". it is a well known eye disease in Indonesia, since many districts have their specific names for trachoma. The progress of trachoma depends on sociohygienic condition in the environment. The progress of trachoma in an area is indicated by its frequency in the area.An investigation of the disease among pupils will give a lower frequency than in the community, but it is valid as a parameter of the progress of the disease.Key Words: communicable disease - trachoma eradication - school health units - keratoconjunctivitis - trachoma